Effects of grain type on growth and performance of steers limit-fed grain-based diets - R.D. Hunter; T. Nutsch; Evan C. Titgemeyer; James S. Drouillard (Kansas Agricultural Experiment Station Research Reports, 1999)
Five hundred fifty two steers were used in a growth experiment designed to evaluate the use of grain sorghum in a limit-feeding program. Dry-rolled corn, dry-rolled grain sorghum, steam-flaked grain sorghum, or combinations of grains totaled 70% (dry matter basis) of the diet. Daily intakes were restricted to 2% of body weight (dry matter basis). Cattle were fed their assigned diet for 95 days followed by a 5- day period on a common diet to compensate for differences in gut fill. Steam-flaked grain sorghum and dry-rolled corn yielded similar gain efficiencies and average daily gains. Dry-rolled grain sorghum, however, had 71% the value of dry-rolled corn and 72% the value of steamflaked grain sorghum. These values became 80% and 83% when the 5 days on a common diet were considered. No significant associative effects were observed for the combinations of grains. The data clearly indicate that grains that are slowly fermented (i.e. dry-rolled grain sorghum) are less desirable in a limit-feeding program. Differences among grains observed in full-fed, finishing diets will likely be as great or greater with high-grain, limit-fed diets. Consequently, extensive processing of grain sorghum would be as beneficial in a limit-fed ration for growing cattle as it is perceived to be in a fullfed, finishing diet.
Keywords: Cattlemen& #x27; s Day; 1999; Kansas Agricultural Experiment Station contribution; no. 99-339-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 831; Beef; Grain sorghum; Limit feeding; Grain processing